A Descriptive Study on Students’ Perceptions About The Foreign Volunteer’s Roles in Learning Process of The Seventh Grade at Smpn 2 Glagah Banyuwangi in 2015/2016 Academic Year - Amalia, Rizki (LUNAR, 2018)
Perception is the experience about objects, events, or the relations that are gotten by concluding the information and interpreting the mesagge. The more complex definition is given by Pareek in Alex (2003:446) who states that perception is a process of receiving, selecting, organizing, interpreting, evaluating, and giving relation to stimulate of the sense. Based on the definition above, it can be summarized that perception is a process of recognizing/receiving the stimuli in form of events, objects, or others through the sense, then those stimuli are organized and interpreted, and lastly giving reaction toward them. To achieve the research purposes, this research uses analytic induction. The researcher use theory from Walters that is self perception Self perception is based on self-efficicacy. It means that the perception occurs based on individual mind (intrinsic). Because the student’s appreciate about the foreign volunteer’s role by themselves. They will appreciate does the foreign volunteers give positive or negative impact.Learning with foreign volunteer made the seventh grade’s at SMPN 2 GlagahBanyuwangi more interested to study English and foreign volunteer give big impact to the students, so they can study hard. Based on the result, it is suggested To the teacher it is suggested to imitate the techniques applied by foreign volunteer, or the teacher can consolidate the teacher’s techniques and the foreign volunteer’s techniques. Students should be active, creative and also fun in teaching learning process and be more confident and do not afraid with English lesson. Students should pay attention to teacher explanation.While for the the other researcher, it is suggested to use the information to know the student’s perceptions about the foreign volunteer’s roles in English learning process at SMPN 2 Glagah. The other researcher are also suggested to use it as reference if having similar research